2013
DOI: 10.1177/1534508413493110
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Children’s Perceptions of Parental Involvement in Conjoint Behavioral Consultation

Abstract: Practitioners of Conjoint Behavioral Consultation rely on several sources of information to assist in planning and evaluation of consultation efforts. Parental involvement in the home is an important aspect in Conjoint Behavioral Consultation, yet there are few questionnaires available to practitioners to assess this important construct, particularly those that target children’s self-report. This study examined the factor structure and reliability of a new questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 85 publications
1
4
0
Order By: Relevance
“…The Supported Autonomous Child Involvement subscale was also presented on a 7-point Likert scale where a high score indicated a high level of autonomy. The Controlling Parental Involvement subscale has been reported to have good validity and internal consistency with Cronbach alpha between 0.71 and 0.75 (Rogers et al, 2014). In the present study, both subscales were shown to be internally consistent:…”
Section: Parental Support For Learning Scale (Psls)supporting
confidence: 52%
See 2 more Smart Citations
“…The Supported Autonomous Child Involvement subscale was also presented on a 7-point Likert scale where a high score indicated a high level of autonomy. The Controlling Parental Involvement subscale has been reported to have good validity and internal consistency with Cronbach alpha between 0.71 and 0.75 (Rogers et al, 2014). In the present study, both subscales were shown to be internally consistent:…”
Section: Parental Support For Learning Scale (Psls)supporting
confidence: 52%
“…Three scales meeting criteria were identified measuring children's involvement in the context of children's education, transitioning parenting style from parent authority to mutual reciprocity, and children's influence over purchasing. The three measures were Perceptions of Parents Scales (Robbins, 1994), Parental Support for Learning Scale (Rogers, Markel, Midgett, Ryan, & Tannock, 2014), and Children's Perceptions of their Influence over Purchases Questionnaire (Caruana & Vassallo, 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The scale has four dimensions, namely, parental management of the learning environment, controlling parental involvement, parental participation with homework, and supportive parental involvement. The scale was constructed by Rogers, Tannock, and Midgett [14]. Moreover, the Parental Involvement questionnaire demonstrated excellent reliability in this study, with a Cronbach's alpha value of 0.92.…”
Section: Research Instrumentmentioning
confidence: 70%
“…The Parental Support for Learning Scale ( PSLS : Rogers et al, 2014) was used to assess mothers’ and fathers’ perception of their PIE behaviors and adolescents’ perceptions of their parents PIE behaviors. Exploratory factor analysis of a short version of the scale that did not include the Aspirations scale revealed a two-factor structure: (1) Supportive Involvement (α = 87 and .89) and (2) Controlling Involvement (α = .90 and .89; Rogers et al, 2018).…”
Section: Methodsmentioning
confidence: 99%